2011
DOI: 10.1124/mol.110.070714
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of ATP-Binding Cassette C2 Protein Expression in HepG2 Cells after Rifampicin Treatment Is Mediated by MicroRNA-379

Abstract: microRNAs (miRNAs), which contribute to the post-transcriptional processing through 3Ј-untranslated region-interference, have been shown to be involved in the regulation of ATPbinding cassette (ABC) membrane transporters. The aim of this study was to investigate whether ABCC2, an important efflux transporter for various endogenous and exogenous compounds at several compartment barriers, is subject to miRNAmediated post-transcriptional gene regulation. We screened the expression of 377 human miRNAs in HepG2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 25 publications
6
47
0
Order By: Relevance
“…The reduction of ABCC2 protein expression by rifampicin in HepG2 cells was associated with an increased ABCC2 mRNA level and altered miRNA expression profile (Haenisch et al, 2011). Among these altered miRNAs, miR-379 was elevated and might directly target ABCC2 mRNA.…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 92%
See 1 more Smart Citation
“…The reduction of ABCC2 protein expression by rifampicin in HepG2 cells was associated with an increased ABCC2 mRNA level and altered miRNA expression profile (Haenisch et al, 2011). Among these altered miRNAs, miR-379 was elevated and might directly target ABCC2 mRNA.…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 92%
“…Among these altered miRNAs, miR-379 was elevated and might directly target ABCC2 mRNA. Indeed pre-miR-379 showed a dose-dependent suppression of ABCC2 protein expression in HepG2 cells, and miR-379 antagomir was able to rescue rifampicin-reduced ABCC2 protein expression, demonstrating a mechanistic role for miR-379 in rifampicin-altered ABCC2 protein expression at the posttranscriptional level (Haenisch et al, 2011). Another study showed that miR-297 was able to modulate ABCC2 expression in drug-resistant HCT116 cells and thus increased the efficacy of anticancer drugs (Xu et al, 2012a).…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 97%
“…Previous studies showed that treatment with rifampicin decreased the expression level of ABCC1 (MRP1) in human skin [17] and in HepG2 cells [24]. The effect of rifampicin on the expression of SLC transporters was thus investigated.…”
Section: Effect Of Rifampicin On Gene Expression Of Slc Transporters mentioning
confidence: 99%
“…Some miRNAs (e.g., miR-519c, -328, -326, -379, -1291, and -124) Pan et al, 2009Pan et al, , 2013Liang et al, 2010;Haenisch et al, 2011;Markova and Kroetz, 2014) that negatively regulate the expression of ATP-binding cassette efflux transporters (e.g., ABCC1, ABCC2, ABCC4, and ABCG2) may be used to improve the sensitivity of human carcinoma cells to anticancer drugs. Furthermore, a number of oncogenic miRNAs dysregulated in tumor tissues may be directly targeted to manage tumor progression (Trang et al, 2008;Bader et al, 2010).…”
Section: Introductionmentioning
confidence: 99%